Green marketing as a positive driver toward business sustainability - Naidoo, Vannie, 1972-; Verma, Rahul, 1989- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2020)
"This book examines the various facets of green marketing and the opportunities and challenges it presents to marketers and society"--